2021
DOI: 10.3892/ol.2021.12914
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑malarial drug dihydroartemisinin downregulates the expression levels of CDK1 and CCNB1 in liver cancer

Abstract: Liver cancer is the third leading cause of cancerassociated mortality worldwide. By the time liver cancer is diagnosed, it is already in the advanced stage. Therefore, novel therapeutic strategies need to be identified to improve the prognosis of patients with liver cancer. In the present study, the profiles of GSE84402, GSE19665 and GSE121248 were used to screen differentially expressed genes (DEGs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Our previous study showed DHA inhibited cell growth in HepG2(Hao et al 2021) and HepG2215 cells (Shi et al 2019). To further study the effect of DHA on liver tumor in vivo , C57BL/6 mice with liver tumors in situ were induced by DEN/TCPOBOP (Li et al 2020, Bergmann et al 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study showed DHA inhibited cell growth in HepG2(Hao et al 2021) and HepG2215 cells (Shi et al 2019). To further study the effect of DHA on liver tumor in vivo , C57BL/6 mice with liver tumors in situ were induced by DEN/TCPOBOP (Li et al 2020, Bergmann et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…DHA was a derivative of artemisinin extracted from artemisia annua Linn (Guo 2016). Our previous studies showed that DHA inhibited HepG2 (Hao et al 2021) and HepG2215 cells (Shi et al 2019). Meanwhile, some studies suggested that DHA downregulated PD-L1 expression in non-small cell lung cancer (Zhang et al 2020).…”
mentioning
confidence: 99%
“…miR-582-5p directly inhibited the expression of CDK1 and AKT3, and indirectly inhibited the expression of cyclinD1, thereby regulating HCC [9]. Experiments have also con rmed that dihydroartemisinin (DHA) can reduce the expression level of CDK1, thereby inhibiting the proliferation of liver cancer cells [10]. At present, CDK1 is highly expressed in various tumour tissues to varying degrees, and it has been proved that CDK1 can play an important role in lung cancer [11], breast cancer [12], pancreatic cancer [13], colorectal cancer [14] and so on by regulating the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Lycorine is a potent direct inhibitor of CDK1, which can be utilized for the treatment of HCC [81]. Dihydroartemisinin (DHA) derived from Artemisia annua Linn is another naturally occurring inhibitor of CDK1, which has been shown to inhibit the cyclin B1-CDK1 pathway and HCC cell proliferation [82].…”
Section: Cdk1mentioning
confidence: 99%